Facial and oropharyngeal angioedema with rash: A rare and interesting clinical presentation of systemic lupus erythematosus - Saini, Rohin; Mishra, Arvind; Gupta, Kamlesh K; Kallani, Monika; Anand, Amit; Hashim, Mohammed Hashim (Indian Journal of Case Reports, 2019)
-